2015
DOI: 10.5116/ijme.5658.0a6b
|View full text |Cite
|
Sign up to set email alerts
|

Can enriching emotional intelligence improve medical students’ proactivity and adaptability during OB/GYN clerkships?

Abstract: ObjectivesThe purpose of this pilot study was to examine our hypothesis that enriching workplace emotional intelligence through resident coaches could improve third-year medical students’ adaptability and proactivity on the Obstetrics and Gynecology clerkship.MethodsAn observational pilot study was conducted in a teaching hospital. Fourteen 3rd year medical students from two cohorts of clerkships were randomly divided into two groups, and equally assigned to trained resident coaches and untrained resident coac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 21 publications
(23 reference statements)
0
24
0
Order By: Relevance
“…Two studies focused on increasing emotional intelligence (EI) in residents and students. Guseh et al cited the correlations between EI and professionalism, academic success and interpersonal skills as a driver for their study. They found that medical students exhibited improved adaptability and proactivity after 6 weeks of coaching.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies focused on increasing emotional intelligence (EI) in residents and students. Guseh et al cited the correlations between EI and professionalism, academic success and interpersonal skills as a driver for their study. They found that medical students exhibited improved adaptability and proactivity after 6 weeks of coaching.…”
Section: Resultsmentioning
confidence: 99%
“…1 Emotional intelligence-based education may also contribute to the teaching of professionalism and communication skills. 2,3 It is perhaps unfortunate that, historically, such great emphasis has been placed on IQ and technical ability, while scant attention has been paid to emotional intelligence. As there is now good evidence that individuals are not born with the latter, but that it can be acquired, now is perhaps the time for educators, as well as clinicians themselves, to modify preand postgraduate curricula and training accordingly.…”
Section: Resultsmentioning
confidence: 99%
“…Residents were identified more strongly as key contacts by the elective students in our study rather than consultants. It was mentioned that residents untrained in the guidance of elective students often step in as supervisors [ 28 ], which has a negative impact on the interaction of students and supervisors and thus on the students’ SOL; also, trainings of residents in emotional intelligence are helpful in encouraging self-initiative and thus SOL of elective students [ 29 ]. Likewise, the mentoring by physicians desired by students during clinical electives is beneficial for SOL and does not seem to pose an additional burden on the residents [ 30 ].…”
Section: Discussionmentioning
confidence: 99%